The Dependence of the Absorption Coefficient of X-Rays on the Position of the Vectors of Diffraction and Temperature Gradient - Hayrapetyan, K. T.; Noreyan, S. N.; Margaryan, V. V.; Kocharyan, V. R.
The behavior of the interference absorption coefficient of X-rays in Laue geometry depending upon the disposition of diffraction vector and temperature gradient vector in the perpendicular direction to the reflecting atomic planes family was experimentally studied. The study was carried out for the different thicknesses of quartz single crystal for atomic planes (101 ̅1). It was shown that in the case of anti-parallel disposition of the diffraction vector and temperature gradient vector the absorption coefficient of X-rays sharply decreases with the increase of temperature gradient and in the case of the parallel disposition of the diffraction vector and the temperature gradient vector the absorption coefficient firstly increases and then decreases. The theoretical calculation corresponding to the experiment conditions have been done. The physical explanation of the obtained experimental results has been made. The obtained results are in good correspondence with the experiment.
Keywords: Physics; Optics